Antidiarrheal, analgesic,antidepressant, antimicrobial and hypoglycemic activities of methanolic extract from Sonneratia apetala fruit, with identification of bioactive compounds in n-hexane, chloroform, and ethyl acetate fractions - Fatema Akhter; Md. Ripaj Uddin; Muhammad Abdullah Al Mansur; Mohammad Saydur Rahman; Md. Ahedul Akbor; Nahida Akter; Abubakr M. Idris; Md. Golam Mostafa; AHM Shofiul Islam Molla Jamal; Sarker Kamruzzaman (PLoS ONE, 2025)
The rapidly growing mangrove fruit Sonneratia apetala, native to the deltaic region of Bangladesh, holds promise in traditional medicine due to its bioactivity and antimicrobial properties. Sample collections from Nijum Dwip, Hatiya, Noakhali in Bangladesh were divided into pericarps and seeds, subsequently fractionated with methanol, n-hexane, ethyl acetate, and chloroform. Bioactivity assays involved Swiss albino mice, acquired from ICDDR, B, in compliance with FELASA standards. Standard agents such as diclofenac sodium, loperamide, diazepam, and glibenclamide were used to evaluate antidiarrheal, antidepressant, hypoglycaemic, and analgesic effects, while ciprofloxacin served as a reference for antibacterial and antifungal testing. Methanolic extracts (ME) of the seed and pericarp exhibited notable peripheral and central analgesic effects at 200 and 400 mg/kg dosages. The ME of seeds demonstrated the strongest antidiarrheal efficacy at 400 mg/kg after 1 hour, and the pericarp at 200 mg/kg after 2 hours. The ME also showed significant antidiabetic potential in both seed (99%) and pericarp extracts. GC-MS analysis disclose seven bioactive compounds in the n-hexane, ethyl acetate, and chloroform fractions, including N-Ethyl-2-methylbenzenesulfonamide, 3,6-Pyridazinedione, 1,2-dihydro-1-(4-nitrophenyl), N-Acetyl-alpha-aminooxybutyric acid (methyl), 2H-Phenanthro[2,1-b] azepin-2-one (1,3,4,5,5a), and Undecane. These compounds have established anticancer and antimicrobial properties. Both pericarp and seed extracts displayed strong antifungal activity against Saccharomyces cerevisiae, Candida albicans, and Aspergillus niger, while moderate antibacterial effects were noted against gram-negative strains like Pseudomonas aeruginosa and Salmonella Typhi as well as gram-positive bacteria such as Staphylococcus aureus. These findings underscore S. apetala’s potential as a valuable bioactive source for traditional medicinal applications.